Technologies for Medical Sciences - Natal Jorge, Renato M. (Lecture Notes in Computational Vision and Biomechanics, 2012)
This book presents novel and advanced technologies for medical sciences in order to solidify knowledge in the related fields and define their key stakeholders.   The fifteen papers included in this book were written by invited experts of international stature and address important technologies for medical sciences, including: computational modeling and simulation, image processing and analysis, medical imaging, human motion and posture, tissue engineering, design and development medical devices, and mechanic biology. Different applications are treated in such diverse fields as biomechanical studies, prosthesis and orthosis, medical diagnosis, sport, and virtual reality.   This book is of interest to researchers, students and manufacturers from  a wide range of disciplines related to bioengineering, biomechanics, computational mechanics, computational vision, human motion, mathematics, medical devices, medical image, medicine and physics.